Perkembangan Desa Marindal I sebagai Daerah Hinterland Kota Medan (Studi Pendekatan dan Analisis Tipologi Desa) - Akhmad Syarif; Marlon Sihombing; Tarmizi Tarmizi (Universitas Negeri Medan, 2014)
The result of the research showed that Marindal I village fell under self-supporting village. The determinant factors of village typology indicated that Marindal I village tended to have the characteristic of urban life, viewed from the population density of 2.692 person per square kilometer. 98.59 % of the people’s livelihood at Marindal I village was non –agrarian. Education at Marindal I village made it a self-supporting village or developing village because 92,49 % of its people were SD (Elementary School)graduates. Custom at Marindal I village was no strict, were only three adat ceremonies. In village equipment and infrastructure, Marindal I village was in (3,11 %). The people’s social life at this village was not very good, and it seemed that it lacked of sense of togetherness. Netherless the deveolpment pattern of Marindal I village as the hinterland tended to be progressive